Pembelajaran Sejarah Online Mahasiswa STKIP PGRI Lubuklinggau di Masa Pandemik Covid 19 - Agus Susilo; Andriana Sofiarini (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
The research purposes is to find out the online history learning of STKIP PGRI Lubuklinggau students in the Covid Pandemic period 19. This study used a qualitative description method, researchers directly analyze the lecture system of history education students at STKIP PGRI Lubuklinggau. The results were obtained as follows: 1) general history learning for students, which is basically most of history learning is done face-to-face or outside the field. However, due to the Covid 19 epidemic, historical learning was shifted to online learning. 2) Online History Learning STKIP PGRI Lubuklinggau students in the Covid Pandemic Period 19, namely students of STKIP PGRI Lubuklinggau history education are required to conduct online learning to support. The continuation of online learning in the Covid 19 period, made learning history more interesting. Nevertheless, direct learning is still expected in the future. The conclusions of the study are: online learning can be a solution for students of history education in attending lectures during the Covid 19 epidemic. Keywords: Online, STKIP PGRI Lubuklinggau, Pandemic